Is there only one species of Hepatozoon infecting Brazilian caimans? Integrative taxonomy unveiling the parasite’s diversity - Úngari, L. P. [UNESP]; Netherlands, E. C.; Santos, A. L.Q.; Viana, L. A.; da Silva, R. J. [UNESP]; O’dwyer, L. H. [UNESP] (FapUNIFESP (SciELO), 2024)
Hepatozoon spp. are the most common haemoparasites reported from reptiles around the world, however, only six species have been described infecting crocodilians. In Brazil, Hepatozoon caimani Carini, 1909 is currently the only recognized species from the caiman hosts. This study provides new data on the diversity of species of Hepatozoon infecting Caiman crocodilus (Linnaeus) using molecular data and phylogenetic analysis, with additional support of morphological data of developmental stages from host blood and tissue. Forty-four individuals were collected and screened for haemogregarines, and blood and tissue samples were analysed by light microscopy with 31 (70.45%) infected. Hepatozoon spp. blood developmental stages included immature and mature gamonts with or without cytoplasmic vacuoles and free gamonts. Additionally, merogonic developmental stages were found in the liver and spleen of infected hosts. Based on the morphological and molecular data, this study identified two possible different species of Hepatozoon, being one of them the H. caimani with intragenotypic divergence.
Há somente uma espécie de Hepatozoon infectando caimans brasileiros? Taxonomia integrativa desvendando essa diversidade parasitária
Keywords: Brazil; crocodilian; diversity; Hemogregarine; PCR